A Study on GST & Its Impact on Pricing of Carpets & Floorings Industry in India - Garg, Yogesh; Anand, Neeta (International Journal of Computer Sciences and Engineering, 2019)
The implementation of GST in India was considered to be major tax reform, since Independence. The research paper focuses on the impact of goods & service tax on the pricing of Indian carpet & flooring industry. The GST has not only provide full set off for input tax but also abolish the burden of several existing taxes viz Central Excise Tax, VAT/Sales Tax, Service tax etc. There was fear among the contributors of tax that the cost of goods might go up, harassment would be more and so on. This study is an attempt to examine the pre and post GST regime and, the pros and cons of old as well as the new tax system on the pricing of carpet & flooring industry. There are mixed opinion & response among the manufacturers & traders of carpet industry. Therefore, it is an attempt to compare past tax structure and current GST regime in India.